1965
DOI: 10.1038/icb.1965.63
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Skin Calcifying System

Abstract: Summary. Histological changes aud tbe accretion of calcium ami phrwphonis in au expi'iinicnhilly induced calcification of rat skin ("topical calcipliylaxis") have been described. Tbe appearance of mineral deposits was rapid and mild injury (epilatiou or light .squeezing) was sufficient stimulus tt> eause a sparse, restrieted mineralisation wbicb, with prior treatment of the animal witb an hyperealeaemie agent, progressed to give a grossly mineralised skin area. The initial mineralisation wa.s restricted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Using epilation as a challenger, Cousins and Smfllie [4] found that initial mineralization was restricted to the hair follicles and that phosphate uptake preceded that of calcium. Employing a similar procedure, Moss and Urist [9] reported an initial increase of calcium at sites of mineralization.…”
Section: Introductionmentioning
confidence: 98%
“…Using epilation as a challenger, Cousins and Smfllie [4] found that initial mineralization was restricted to the hair follicles and that phosphate uptake preceded that of calcium. Employing a similar procedure, Moss and Urist [9] reported an initial increase of calcium at sites of mineralization.…”
Section: Introductionmentioning
confidence: 98%
“…after injury but that this is no longer present at 12 hr. These findings relate to the non-dosed animal, i.e., the situation where mineralisation does not progress beyond the involvement of hair follicles (Cousins and Smillie, 1965). By 12 hr.…”
Section: Resultsmentioning
confidence: 98%
“…It has been pointed out (Cousins and Smillie, 1965) that in the skin system both coUagenous and keratinous matrices calcified, although the latter did preferentially. The widespread occurrence of calcification in various vertebrate and invertebrate species serves to remove emphasis from any particular protein, and there are many recorded instances of calcification associated with non-collagenous matrices (Pautard, 1961;Blakey, Earland, Stell and Swift, 1965;Martin, Schiffmann, Bladen and Nylen, 1963).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations